Cryopreservation of Mesenchymal Stromal Cells within Wide-Porous Three-Dimensional Alginate-Gelatin Scaffolds - Petrenko, Yuri A.; Katsen-Globa, Alisa; Meiser, Ina; Ivanov, Roman V.; Lozinsky, Vladimir I.; Zimmermann, Heiko; Petrenko, Aleksandr Y. (Problems of Cryobiology and Cryomedicine, 2013)
N/AProbl Cryobiol Cryomed 2013; 23(4):351–354.